Structural and biochemical characterization of the novel serpin Iripin-5 from Ixodes ricinus - Kascakova, Barbora; Kotal, Jan; Martins, Larissa Almeida; Berankova, Zuzana; Langhansova, Helena; Calvo, Eric; Crossley, Joel A; Havlickova, Petra; Dycka, Filip; Prudnikova, Tatyana; Kuty, Michal; Kotsyfakis, Michail; et al. (Acta crystallographica. Section D, Structural biology, 2021)
Iripin-5 is the main Ixodes ricinus salivary serpin, which acts as a modulator of host defence mechanisms by impairing neutrophil migration, suppressing nitric oxide production by macrophages and altering complement functions. Iripin-5 influences host immunity and shows high expression in the salivary glands. Here, the crystal structure of Iripin-5 in the most thermodynamically stable state of serpins is described. In the reactive-centre loop, the main substrate-recognition site of Iripin-5 is likely to be represented by Arg342, which implies the targeting of trypsin-like proteases. Furthermore, a computational structural analysis of selected Iripin-5-protease complexes together with interface analysis revealed the most probable residues of Iripin-5 involved in complex formation.
Keywords: Ixodes ricinus; serine protease inhibitors; klíště; serpins; Iripin-5; Enzyme Inhibitors; serpiny; králíci; neutrofily; tick saliva; kultivované buňky; Animals; X-ray structure; zvířata; makrofágy; Serpins; myši inbrední C57BL; Rabbits; erytrocyty; myši; Erythrocytes; Ixodes; Neutrophils; Mice, Inbred C57BL; Cells, Cultured; antiflogistika; Anti-Inflammatory Agents; Mice; Macrophages; inhibitory enzymů